Microalgae as substrate in low cost terracotta-based microbial fuel cells: Novel application of the catholyte produced. (June 2016) - Salar-García, M.J.; Gajda, I.; Ortiz-Martínez, V.M.; Greenman, J.; Hanczyc, M.M.; de los Ríos, A.P.; Ieropoulos, I.A.
Graphical abstract: Highlights: Novel application of the catholyte produced in ceramic MFCs to lyse microalgae. Microalgae as a potential low cost co-substrate for MFCs. Light/dark cycle assisted microalgae digestion in the presence of catholyte. Abstract: In this work, the by-product generated during the operation of cylindrical MFCs, made out of terracotta material, is investigated as a feasible means of degrading live microalgae for the first time. In addition to the low cost materials of this design, the reuse of the solution produced in the cathode renders the technology truly green and capable of generating bioenergy. In this study, the effect of a light/dark cycle or dark conditions only on the digestion of live microalgae with the catholyte is investigated. The results show that a combination of light/dark improves degradation and allows algae to be used as substrate in the anode. The addition of 12.5 mL of a 1:1 mix of catholyte and microalgae (pre-digested over 5 days under light/dark) to the anode, increases the power generation from 7 μW to 44 μW once all the organic matter in the anode had been depleted.